Chemical Changes of Enamel Produced by Sodium Fluoride, Hydroxyapatite, Er:YAG Laser, and Combined Treatments - Alma Yadira Ceballos-Jiménez; Laura Emma Rodríguez-Vilchis; Rosalía Contreras-Bulnes; Jesús Arenas Alatorre; Rogelio José Scougall-Vilchis; Ulises Velazquez-Enriquez; María de los Angeles Moyaho-Bernal (Journal of Spectroscopy)
Occlusal pits and fissures of permanent molars are considered to have higher risk of developing caries. Enamel demineralization can be prevented by applying remineralizing agents, and their absorption increases with prior irradiation. This work evaluates the chemical changes produced by treating occlusal surfaces with sodium fluoride (NaF), hydroxyapatite-NaF-xylitol (HA-NaF-X), Er:YAG laser irradiation (L), and combinations thereof. Fifty enamel samples were randomly assigned to five groups (n=10): NaF, HA-NaF-X, L, L + NaF, and L + HA-NaF-X. The chemical composition of human enamel was evaluated before (BT) and after (AT) treatment using energy-dispersive X-ray spectroscopy (EDS) and expressed in atomic percentages (at%). For combined treatment groups, the products were applied after laser irradiation. The statistical analyses included a paired t-test and ANOVA (p≤0.05). After treatment, a significant increase in F at% was observed in the NaF group (2.71 ± 1.41). The irradiated groups showed significant increases in Ca and P at% and the Ca/P ratio. The highest values occurred for L + NaF (30.44 ± 4.28 Ca at%, 11.97 ± 1.45 P at%, and 2.55 ± 0.22 Ca/P ratio). Er:YAG laser irradiation alone or in combined protocols increased the Ca and P content of dental enamel, in vitro.